Change in Muscle Oxygenation During Stretches of Different Intensities and Durations - MINAMI, Yoriyasu; KASIWAGI, Ayana; MORISAWA, Tomoyuki; OOTSUKA, Shota; NAKASIMA, Shogo; TAKAHASI, Tetsuya (Rigaku ryoho kagaku, 2012)
[Purpose] The purpose of this study was to investigate how long and how much muscle stretching would cause a change in muscle oxygenation. [Subjects] Seventeen healthy young volunteers participated in this study. [Methods] Four types of manual passive stretching (5 N·m) for 60 sec and for 120 sec, 10 N·m for 60 sec and for 120 sec) were randomly performed by the calf muscle. Near-infrared spectroscopy muscle oxygenation of the calf muscle was monitored during passive stretching. [Results] Muscle oxygenation in the calf muscle during passive stretching of 10 N·m for 120 sec decreased significantly compared with that during the other three types of passive stretching. The difference of muscle oxygenation in the calf muscle between passive stretching at 5 N·m and passive stretching at 10 N·m became significant as the stretch time increased. [Conclusion] Theresults suggest that a certain level of strength and time are indispensable for decreasing the muscle blood flow and to causing sufficient metabolic change during passive stretching.